1970
DOI: 10.3126/nelta.v14i1.3093
|View full text |Cite
|
Sign up to set email alerts
|

Learners' Errors and their Evaluation

Abstract: This study identifies, describes and evaluates the learners' errors, and determines the gravity of those errors in terms of intelligibility and acceptability by the Nepali, non-Nepali and native English speaking teachers. This study was targeted at the grammatical errors and perceptions of different English teachers on those errors. The research findings were analyzed and expressed quantitatively. The study revealed that the Nepali English teacher evaluators were found to be the most severe judges. The non-Nep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…Similar to the results of the present study, Lin (2002) found the four highest error frequencies as sentence structures (30.43 %), wrong verb forms (21.01%), sentence fragments (15.94%), and wrong use of words (15.94%) respectively. In her study conducted with Nepali students and teachers, Maharjan (2009) investigated grammatical errors made by the students and explored perceptions of different English teachers' views about these errors. She reported that tense held the highest level of difficulty for the students, where they committed errors at 25.16%.…”
Section: Discussion Conclusion and Recommendationsmentioning
confidence: 99%
“…Similar to the results of the present study, Lin (2002) found the four highest error frequencies as sentence structures (30.43 %), wrong verb forms (21.01%), sentence fragments (15.94%), and wrong use of words (15.94%) respectively. In her study conducted with Nepali students and teachers, Maharjan (2009) investigated grammatical errors made by the students and explored perceptions of different English teachers' views about these errors. She reported that tense held the highest level of difficulty for the students, where they committed errors at 25.16%.…”
Section: Discussion Conclusion and Recommendationsmentioning
confidence: 99%
“…It has been prioritized in the educational curriculum. Bhattarai (2006) and Maharjan (2009) assert that English still has the status of a foreign language in Nepal, because there are still no communities that use English for day to day conservations.…”
Section: Status Of English In Nepalmentioning
confidence: 99%